Plan de marketing para el desarrollo turístico en la comunidad de Maca Chico, de la parroquia Poaló del cantón Latacunga, período 2014-2015 - Tarco Guamushig, Mayra Fernanda (2015)
The present investigation has as objective to positioning and to publicize the tourist attractions, based on a marketing plan for tourism development in the Maca Chico Community of the Poalo parish, Latacunga canton, with the purpose of improving people’s life level, that is why strategies have been considered for achieve objectives, for this work the methodology applied was research which consists of a qualitative and quantitative approach, which will be exclusively for the observation and evaluation of the phenomenon, those reflected through surveys, to meet the needs of the market….